PENGUATAN DESA ENERGI BERDIKARI BERBASIS BIOGAS MELALUI PENDEKATAN ECO-LOKALISME DI DESA MARGA TABANAN - I Wayan Eka Mahendra; Ni Nyoman Parmithi; I Nyoman Bagus Suweta Nugraha (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
This community service program aimed to strengthen the implementation of an independent energy village through biogas development using an eco-localism approach in Marga Village, Tabanan Regency. The program was conducted in response to increasing household energy demands, dependence on fossil fuels, and environmental pollution caused by unmanaged cattle waste. The eco-localism approach emphasized the utilization of local resources, community participation, and sustainable environmental management to support renewable energy development at the village level. The methods applied in this program included Participatory Rural Appraisal (PRA), observation, Focus Group Discussion (FGD), socialization, technical training, mentoring, and direct implementation of biogas management from cattle manure. The results demonstrated that the program successfully increased community awareness and participation in renewable energy management. Community participation reached approximately 90% during training and implementation activities, while household dependence on LPG decreased by around 60% after utilizing biogas for cooking needs. In addition, bioslurry produced from the biogas process was utilized as organic fertilizer, reducing chemical fertilizer use by approximately 40%. The program also improved environmental sanitation by reducing livestock waste accumulation and unpleasant odors around cattle farms. Therefore, the eco-localism-based biogas program has strong potential to support sustainable village energy independence and environmentally friendly community empowerment in rural areas.